Diversity and composition of bacterial endophytes among plant parts of Panax notoginseng - Linlin Dong; Ruiyang Cheng; Lina Xiao; Fugang Wei; Guangfei Wei; Jiang Xu; Yong Wang; Xiaotong Guo; Zhongjian Chen; Shilin Chen (BMC, 2018)
Abstract Background Bacterial endophytes are widespread inhabitants inside plant tissues that play crucial roles in plant growth and biotransformation. This study aimed to offer information for the exploitation of endophytes by analyzing the bacterial endophytes in different parts of Panax notoginseng. Methods We used high-throughput sequencing methods to analyze the diversity and composition of bacterial endophytes from different parts of P. notoginseng. Results A total of 174,761 classified sequences were obtained from the analysis of 16S ribosomal RNA in different parts of P. notoginseng. Its fibril displayed the highest diversity of bacterial endophytes. Principal coordinate analysis revealed that the compositions of the bacterial endophytes from aboveground parts (flower, leaf, and stem) differed from that of underground parts (root and fibril). The abundances of Conexibacter, Gemmatimonas, Holophaga, Luteolibacter, Methylophilus, Prosthecobacter, and Solirubrobacter were significantly higher in the aboveground parts than in the underground parts, whereas the abundances of Bradyrhizobium, Novosphingobium, Phenylobacterium, Sphingobium, and Steroidobacter were markedly lower in the aboveground parts. Conclusions Our results elucidated the comprehensive diversity and composition profiles of bacterial endophytes in different parts of 3-year-old P. notoginseng. Our data offered pivotal information to clarify the role of endophytes in the production of P. notoginseng and its important metabolites.